Kinematic analysis of three water polo front crawl styles - de Jesus, K.; Figueiredo, P.; de Jesus, K.; Pereira, F.; Vilas-Boas, J. P.; Machado, L.; Fernandes, R. J. (Journal of Sports Sciences, 2012)
During water polo matches, players use different front crawl styles. The purpose of this study was to conduct a kinematic analysis of three water polo front crawl styles: front crawl with head under water, front crawl with head above water, and front crawl when leading the ball. Ten proficient water polo players performed 3 × 15 m sprints in each front crawl style, which were recorded three-dimensionally by two surface and four underwater cameras. The results showed no differences in performance and several kinematic characteristics among the water polo front crawl styles. However, front crawl when leading the ball showed shorter stroke length and greater stroke frequency. Front crawl with head underwater presented greater maximal finger depth and elbow angle at mid-stroke position. Front crawl with head above water and when leading the ball showed greater trunk obliquity and maximal depth of right and left foot, and shorter kick stroke frequency. The findings suggest that proficient players learn to master front crawl with head above water to achieve top velocity. Despite the common use of the front crawl with head underwater as the basis for water polo fast displacement, coaches should emphasize the use of the specific water polo styles to attain high performance.